La construction des échelles de la sécurité maritime dans un contexte d’intégration régionale : le cas de la grande région Caraïbes et ses façades Atlantique et Pacifique - Sylvain Domergue (Cybergeo, 2020)
This paper examines the building process of maritime security in a context of regional integration, focusing on the Wider Caribbean Region and its Atlantic and Pacific seaboard. Based on research conducted on three continents with several national and regional institutions and interviews with various players in the security, diplomatic and maritime fields, this study aims to analyse the way in which States and international organisations perceive and adapt to regional maritime threats in space, in a coordinated or uncoordinated manner. It also aims to analyse how and to what extent these security constraints and responses can be a vector for strengthening regional political integration processes. By presenting a typology and spatial manifestations of active maritime threats in this area, this article first highlights a certain "community of destiny" of the States and international organisations of the region faced with these issues. The results show that the construction of security systems is mainly structured on a sub-regional scale, generally favouring geographical and political proximity, often relying on pre-existing regional institutions. The article also highlights a correlation between the political fragmentation of maritime space and increased vulnerability to direct and indirect risks.